PENGARUH VARIASI PRODUK, SALES PROMOTION DAN HARGA TERHADAP KEPUASAN KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA TOKO EO COFFEE ARJASA SITUBONDO - Bagus Rahmat Hidayat; Ediyanto Ediyanto; Lusiana Tulhusnah (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the Effect of Product Variation, Sales Promotion and Price on Consumer Satisfaction with Purchasing Decisions as Intervening Variables at the EO Coffee Arjasa Situbondo Store. The sampling technique used in this study was simple random sampling of 97 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The test results show that Product variation has a positive and significant effect on Purchasing Decisions, Sales promotion has a significant effect on Purchasing Decisions, Price has a positive but not significant effect on Purchasing Decisions, Product variation has a negative but significant effect on Consumer Satisfaction, Sales promotion has a positive and significant effect on Consumer Satisfaction, Price has a positive but not significant effect on Purchasing Decisions, Purchasing Decision has a positive and significant effect on Consumer Satisfaction, Product variation has a positive and significant effect on Consumer Satisfaction through Purchasing Decisions, Sales promotion has a positive and significant effect on Consumer Satisfaction through Purchasing Decisions purchase, Price has a positive but significant effect on Consumer Satisfaction through Purchasing Decisions.